Alteration of the blood-brain barrier by COVID-19 and its implication in the permeation of drugs into the brain - Hernández-Parra, Héctor; Reyes-Hernández, Octavio Daniel; Figueroa-González, Gabriela; González-Del Carmen, Manuel; González-Torres, Maykel; Peña-Corona, Sheila I.; Florán, Benjamín; Cortés, Hernán; Leyva-Gómez, Gerardo (Frontiers in Cellular Neuroscience, 2023)
Diverse neurological symptoms have been reported in patients with SARS-CoV-2 disease (COVID-19), including stroke, ataxia, meningitis, encephalitis, and cognitive impairment. These alterations can cause serious sequelae or death and are associated with the entry of SARS-CoV-2 into the Central Nervous System (CNS). This mini-review discusses the main proposed mechanisms by which SARS-CoV-2 interacts with the blood-brain barrier (BBB) and its involvement in the passage of drugs into the CNS. We performed a search in PubMed with the terms “COVID-19” or “SARS-CoV-2” and “blood-brain barrier injury” or “brain injury” from the year 2019 to 2022. We found proposed evidence that SARS-CoV-2 infects neurovascular cells and increases BBB permeability by increasing the expression of matrix metalloproteinase-9 that degrades type IV collagen in the basement membrane and through activating RhoA, which induces restructuring of the cytoskeleton and alters the integrity of the barrier. The breakdown of the BBB triggers a severe inflammatory response, causing the cytokine storm (release of IL-1β, IL-6, TNF-α, etc.) characteristic of the severe phase of COVID-19, which includes the recruitment of macrophages and lymphocytes and the activation of astrocytes and microglia. We conclude that the increased permeability of the BBB would allow the passage of drugs that would not reach the brain in a normal physiological state, thus enhancing certain drugs’ beneficial or adverse effects. We hope this article will encourage research on the impact of drugs on patients with COVID-19 and recovered patients with sequelae, focusing mainly on possible dose adjustments and changes in pharmacokinetic parameters.